Diary of a wimpy kid double down - Kinney, Jeff (New York Amulet Books, 2016)
Greg Heffley's mom wants him to take a break from video games while Halloween approaches and he comes up with an idea to make a movie
2
Keywords: Diaries -- Fiction; Family life -- Fiction; Halloween -- Fiction; Humorous stories; Motion pictures -- Production and direction -- Fiction